Tracing Spirituality through The Great Kapok Tree, Greta and The Giants, and The Lorax Novels: A Kincentric Ecology Perspective - Erina Putri; Thohiriyah , Thohiriyah (Universitas Negeri Semarang, 2024)
Through children's literature, kincentric ecology is investigated to convey spirituality. Kincentric ecology, which emphasizes the interconnectedness of all living beings, provides a framework for understanding how narrative can promote a spiritual connection with nature. Using The Great Kapok Tree, Greta and The Giants, and The Lorax as examples, this study illustrates how ecological themes are used to illustrate the importance of a deep connection with the environment. According to the findings, Children's literature can effectively promote a kincentric viewpoint. Readers are encouraged to develop a more profound appreciation for the natural world and stewardship of the environment through this process.